Expert? What does that mean? Describing the Term "Expert" in Agricultural Communications, Education, Extension, and Leadership Research - Lori M Costello; Tracy Rutherford (Journal of Applied Communications, 2019)
Expertise is dynamic, domain specific, and characterized according to an individual’s level of knowledge, experience, and problem-solving ability. Having expertise in the phenomenon under investigation can be used as an indicator of an individual’s aptitude to effectively serve as a coder in a content analysis or as panelist in a Delphi study. The purpose of this study was to assess 10 years of scholarship published in the premier journals of agricultural education and describe the ways researchers in agricultural communications, education, extension, and leadership disciplines who use content analysis and Delphi study methods are describing the qualifications of the people serving as expert coders and panelists. The study findings revealed the majority of researchers publishing in the premier agricultural education journals are not describing the qualifications used in selecting coders or the credentials the coders possess that would make them qualified to code the data in a content analysis. Furthermore, researchers were inconsistent citing literature that supported their selection of content analysis coders and citing literature to support a decision to describe or not to describe coders’ qualifications. However, a description of Delphi study panelists’ qualifications and citations to support why panelists were selected in a Delphi study were present in all of the Delphi studies analyzed over the 10-year period. Based on these findings, it was concluded that ACEEL researchers should include a description of coder credentials to enhance the consistency, transparency, replicability, rigor, and integrity of ACEEL research. Editors and research professionals who perform journal article reviews for the premier agricultural education journals are encouraged to note the exclusion of a description of content analysis coders’ credentials as part of the peer review process.
Keywords: expert; expertise; content analysis; Delphi study; qualitative description